Spectrum of Pediatric Autoimmune Liver Disease and Validation of Its Diagnostic Scores in Indian Children. Issue 4 (October 2018) - Sood, Vikrant; Lal, Bikrant Bihari; Rawat, Dinesh; Khanna, Rajeev; Rastogi, Archana; Bihari, Chhagan; Kumar, Guresh; Alam, Seema
ABSTRACT: Objectives: There is limited literature on the spectrum of pediatric autoimmune liver disease (AILD, encompassing both autoimmune hepatitis/AIH and autoimmune sclerosing cholangitis [ASC]) in Asian populations and its diagnostic scores similarly require further validation. This work thus aimed to study the clinical characteristics, and to validate available diagnostic criteria in the local pediatric AILD cohort. Methods: A review of all pediatric AILD cases, presenting over a 6-year (2011–2017) period was done, along with comparison of the available diagnostic scores: original (1999), simplified (2008) score, and new proposed (2017) score. Results: A total of 85 subjects (AIH = 70 and ASC = 15) were diagnosed as having AILD. Majority of the cases in both groups presented with advanced hepatic disease (portal hypertension and/or hepatic decompensation). Overall 38 (44.7%) subjects had extrahepatic autoimmune disorders. Good outcome (survival with native liver with medically controllable disease), was seen in 80% AIH subjects, while poor outcome (death/need for liver transplantation or LT) was seen in 13% subjects, with similar results in the ASC cohort. All the 3 available scores had area under receiver operating characteristic (AUROC) curves exceeding 0.9 suggestive of excellent discrimination of AILD (to non-AILD patients), with no statistical difference between them ( P >0.05). Conclusions: In Indian subcontinent, pediatric AILD subjects usually present with advanced hepatic disease, but may have a good outcome if timely therapy can be instituted. Associated autoimmune disorders should be carefully screened. There is no difference in the predictive value of the available diagnostic scores for pediatric AILD. Abstract : Supplemental Digital Content is available in the text